LEGAL PROTECTION OF DISCOTIQUE WORKERS AGAINST NOISE EFFECT IN HEALTH LAW PERSPECTIVE - Ronal Hasudungan Sianturi; Kartina Pakpahan; Naek Silitonga (International Journal of Latin Notary, 2021)
Discotheque workers exposure to excessive loud music which classify as the noise at workplace. Noise causes health problems, namely hearing loss. Discotheque workers need to get legal protection against the impact of noise in the workplace.